PERBEDAAN PRASANGKA SISWA JAWA TERHADAP ETNIS CINA ANTARA SISWA SMA NEGERI 2 UNGARAN DENGANSISWA SMA DON BOSKO SEMARANG - Marista, Yuliana (Empati, 2014)
Prejudice is a negative evaluation of a person or group of people against another person or group, solely because the person or persons that are members of another group different from their own group . Prejudice is a perception of bias because the information is incorrect or incomplete , and partly based on the characteristics of the other groups , both real and imaginary . This study aimed to test empirically the difference between prejudice against ethnic Chinese students of SMAN 2 Ungaran Java and Java students of Don Bosko High School in Semarang .The population in this study is a Java class XI student of SMA 2 Ungaran and students of Don Bosko High School Java Semarang . Sample size was 214 students , which is obtained through cluster random sampling technique from the two schools . Data analysis methods used were t-test technique . Means of data collection in this study is Prejudice Scale ( 32 items Î± = 0.925 ), which has been tested against 66 students of class XI of SMAN 2 Ungaran and students of Don Bosko High School Java Semarang .The results of data analysis using t-test analysis produces values t = -4.923 (p < 0.01 ) . These results indicate that there are significant differences prejudice against ethnic Chinese in Java students at SMAN 2 Ungaran and Don Bosko High School in Semarang .